THE EFFECT OF SUPPORTING ON ADHERENCE TO FE TABLET CONSUMPTION IN ADOLESCENT WOMEN - Rosda Rodhiyana; Rize Budi Amalia; adityawarman adityawarman (Indonesian Midwifery and Health Sciences Journal, 2022)
Background: In Indonesia, the TTD (Tablet Tambah Darah) supplementation program has been carried out in various ways and strategies. Anemia in adolescent girls is still one of the problems that must be solved. In addition to knowledge, factors that can affect the level of compliance indicate that support affects changes in attitudes and behavior in the consumption of Fe tablets. This study aims to analyze the compliance of tablet consumption in adolescent girls in Islamic boarding schools as a strategic effort to determine health policy among female students. Methods: The research method is a cross sectional study; the sampling technique is total sampling with the results of 180 female students. The independent variable is support from the pesantren, while the variable is compliance with Fe tablet consumption. The instrument used is a questionnaire. Data analysis used Spearman Rho test with p value < 0.05. Results: The results showed that there was no relationship between the supporting variables (p=0.222) on the level of adherence to Fe tablet consumption in adolescent girls in Islamic boarding schools Ar-Rohmah Ngawi. Conclusion: The data shows that there is no effect between the support of the pesantren and the level of adherence to the consumption of Fe tablets in adolescent girls.   Keywords: TTD supplementation, anemia for adolescent girls, female students, support, compliance